The cancer‐testis antigen BORIS phenocopies the tumor suppressor CTCF in normal and neoplastic cells. Issue 7 (2nd May 2013) - Tiffen, Jessamy C.; Bailey, Charles G.; Marshall, Amy D.; Metierre, Cynthia; Feng, Yue; Wang, Qian; Watson, Sarah L.; Holst, Jeff; Rasko, John E.J.
Abstract : BORIS and CTCF are paralogous, multivalent 11‐zinc finger transcription factors that play important roles in organizing higher‐order chromatin architecture. BORIS is a cancer‐testis antigen with a poorly defined function in cancer, although it has been hypothesized to exhibit oncogenic properties. CTCF, however, has been postulated as a candidate tumor suppressor. We collated the genetic lesions in BORIS and CTCF from multiple cancers identified using high‐throughput genomics. In BORIS, nonsense and missense mutations are evenly distributed. In CTCF, recurrent mutations are mostly clustered in the conserved zinc finger domain and at residues critical for contacting DNA and zinc ion co‐ordination. Three missense mutations are common to both proteins. We used an inducible lentivector to express wildtype BORIS or CTCF in primary cells and cancer cell lines in order to define their functional differences. Both BORIS and CTCF caused a significant decrease in cell proliferation and clonogenic capacity, without alteration of specific cell cycle phases. Both BORIS and CTCF conferred protective effects in primary cells and some cancer cells during UV damage‐induced apoptosis. Using a bioluminescent MCF‐7 orthotopic breast cancer model in vivo, we demonstrated that CTCF and BORIS suppressed breast cancer growth. These findings provide further evidence that CTCF behaves as a tumor suppressor, and show BORIS has a similar growth inhibitory effect in vitro and in vivo . Hence, acquired zinc finger mutations may disrupt these functions, thereby contributing to tumor growth and development. Abstract : What's new? BORIS and CTCF are paralogous, multivalent 11‐zinc finger transcription factors that are commonly altered in cancer. CTCF exhibits tumor suppressor activity, while the function of BORIS has not yet been determined. Here the authors collated the genetic lesions in BORIS and CTCF found in multiple cancers using high‐throughput genomics. While CTCF mutations occur more frequently in zinc fingers, some CTCF mutations are identical to BORIS mutations. The findings show that BORIS acts like CTCF in decreasing the proliferation and clonogenic capacity of primary and cancer cells in vitro and in vivo and provides a similar protective effect during apoptosis.